Growth and characterization of high-quality bulk hexagonal boron nitride crystals - Li, Jiahan (Kansas State University, 2019)
While hexagonal boron nitride (hBN) in polycrystalline form has met demand for its mechanical, chemical, and thermal applications, its new electronic, optoelectronic, and nanophotonic applications required single crystals with low residual impurity concentrations. Grain boundaries and impurities need to be minimized, as they degrade the properties of hBN that are important for these new applications. The present study was undertaken to develop large area, high quality hBN single crystals at low cost, and with control over its boron isotope concentrations. Furthermore, a preliminary study was undertaken to determine if the properties of hBN could be advantageously altered by irradiation. In this study, four processes to grow and manipulate the properties of hBN single crystals were developed. First, high-quality hBN crystals were grown from an iron metal flux. The quality of crystals produced by this novel, low cost and high purity solvent was equivalent to the best reported in the literature, as verified by Raman spectroscopy, photoluminescence, defect density assessment, and current-voltage measurements. Second, hBN crystals were grown via temperature gradient method with iron-chromium flux. This method has the potential to produce larger, higher quality crystals than the slow cooling method. The maximum crystal domain size was up to 4 mm. Both in- and out-plane thermal conductivity was significantly higher than the hBN grown by slow cooling, indicating improved crystallinity. Third, monoisotopic boron hBN (h¹⁰BN and h¹¹BN) was grown from both Fe and Fe-Cr fluxes. Raman and photoluminescence spectra show the quality of crystal grown from Fe and Fe-Cr fluxes was comparable. Fourth, neutron transmutation doping was studied as a possible method of altering the electrical and optical properties of hBN single crystals. Raman spectroscopy, photoluminescence, and electron paramagnetic resonance spectroscopies established that the effects of neutron irradiation were more pronounced on h¹⁰BN than h¹¹BN. Together, these studies demonstrate the versatility of methods available to produce high quality hBN single crystal with specific properties.
Keywords: hBN single crystals characterization